Strengthening Santri’s Literacy:Optimizing Meta AI to Foster Creative Writing of Islamic Short Stories at Pesantren Baitul Qur'an - Kurniawan, Syamsul; Hanafi, Irfan; Mustain, Muhammad; Sofyan, Anas; Mahiroh, Mar‘ati; Syafi'i, Muhammad (AT-TURATS, 2025)
This article focuses on strengthening santri (students) literacy by optimizing Meta AI technology to foster creativity in writing Islamic short stories at Baitul Qur’an Pontianak. The main argument presented is that integrating adaptive and personalized artificial intelligence can address the challenges of conventional learning models in pesantren (Islamic Boarding School), while simultaneously promoting motivation and higher-order thinking skills in line with the demands of the Society 5.0 era. This article is based on a Community Service Program (Pengabdian kepada Masyarakat) involving collaboration between lecturers and post-graduate students of IAIN Pontianak, who directly implemented a learning intervention using Meta AI as a creative medium. The research employed a Participatory Action Research (PAR) approach, emphasizing active engagement and collective social transformation. The results of the community engagement program demonstrate that the utilization of Meta AI significantly enhances santri’s creativity, productivity, and digital literacy readiness, while reinforcing the spiritual values the pesantren uphold. The significance of this article lies in its contribution to the enrichment of technology-based community service discourse within the context of traditional Islamic education. Furthermore, it is a practical and theoretical reference for similar future initiatives.Artikel ini berfokus pada penguatan literasi santri melalui optimalisasi teknologi Meta AI dalam mendorong kreativitas menulis cerpen Islami di Pondok Pesantren Baitul Qur’an Pontianak. Argumentasi utama dalam tulisan ini adalah bahwa integrasi kecerdasan buatan yang adaptif dan personal mampu menjawab tantangan pembelajaran konvensional di pesantren, sekaligus menumbuhkan motivasi dan kemampuan berpikir tingkat tinggi yang sejalan dengan tuntutan era Society 5.0. Artikel ini lahir dari kegiatan Pengabdian kepada Masyarakat (PkM) yang melibatkan kolaborasi antara dosen dan mahasiswa Pascasarjana IAIN Pontianak, yang secara langsung melakukan intervensi pembelajaran dengan menggunakan Meta AI sebagai media kreatif. Metode penelitian menggunakan pendekatan Participation Action Research (PAR), yang menekankan keterlibatan aktif dan perubahan sosial bersama. Hasil pengabdian menunjukkan bahwa pemanfaatan Meta AI secara signifikan meningkatkan kreativitas, produktivitas, dan kesiapan literasi digital santri, sekaligus memperkuat nilai-nilai spiritual pesantren. Signifikansi artikel ini terletak pada kontribusinya dalam memperkaya kajian pengabdian masyarakat berbasis teknologi dalam konteks pendidikan Islam tradisional, sekaligus menjadi referensi praktis dan teoretis bagi program sejenis di masa depan.